2023
DOI: 10.1002/pon.6177
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver and care recipient health literacy, social support and connectedness on caregiver psychological morbidity: A cross‐sectional dyad survey

Abstract: BackgroundCaregivers play an important role supporting people diagnosed with cancer, yet report significant unmet information and support needs that impact on their psychological wellbeing. Health literacy and social connectedness are key factors that influence wellbeing, yet few studies have examined their relative role in psychological wellbeing of carers. This study investigated relationships between caregiver and care recipient health literacy, social support, and social connectedness on psychological morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Others have found that caregivers without strong social support are more likely to feel burdened and, thus, perceive more of a need for a support intervention. [38][39][40] Future investigators may want to add inadequate social support as a study inclusion criterion to assure that participants are able to benefit from the intervention. We specified that caregivers needed to be caring for the patient for at least 8 hours weekly.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that caregivers without strong social support are more likely to feel burdened and, thus, perceive more of a need for a support intervention. [38][39][40] Future investigators may want to add inadequate social support as a study inclusion criterion to assure that participants are able to benefit from the intervention. We specified that caregivers needed to be caring for the patient for at least 8 hours weekly.…”
Section: Discussionmentioning
confidence: 99%